Using Sencha Touch to build a mobile website - David, Matthew, 1971- (Focal Press, 2011)
Sencha Touch, an open source tool, fills the space between the HTML and the native app. Web apps are generally built using JavaScript but this short ebook shows you how to construct your mobile Web sites using Sencha Touch - you just need to be familiar with Javascript. Sencha Touch targets specific devices, namely iOS, Android 2.1+ and Blackberry 6 devices. Web Apps are a critical element of the future of mobile developmen find out how to easily construct them with this brief intro to Sencha Touch!